Kajian terhadap struktur komuniti tumbuhan Periuk Kera di Hutan Pendidikan Alam, Universiti Kebangsaan Malaysia, Bangi, Selangor Darul Ehsan - H. Adam, Jumaat; H. Daiman, Dayani; Gopir, Geri Kibe; Omar, Ramlan (Universiti Putra Malaysia Press, 2004)
Two species of pitcher plants namely Nepenthes gracilis Korthals and . mirablis (Loureiro) Druce were recorded in the plot with an area of 0.1 hectare. The former species differed from the later species lJy its angular stem, sessile leaves, very thin peristome (~ 1 mm thick), under surface of pitcher lids were sparsely glandular, inner surface of the pitcher cavities were partly covered with exposed type of digestive glands whereas the later species have cylindrical stem, petiolate leaves, thick peristome (;? 1 mm thick), under surface of pitcher lids were densely glandular, inner surface surface of the pitcher cavities were partly covered with overarched type of digestive glands. The population density of N. gracilis is greater than that of N. mirabalis, each contained 147 and 15 individuals respectively. The low density of the former species was attributed to its strong tendency to grow in wet soil particularly in temporary and permanent inundated secondary vegetation. The population dispersion pattern of seedlings, saplings and matured plants of N. gacilis and N. gracilis were significantly aggregated.